(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Cataract is a major causative factor for blindness in India. Cataract extraction is commonest surgery performed both in India and abroad and one of the key procedures for preventable blindness. The popular small incision cataract surgery done for cataract extraction all over the globe for which peribulbar and sub tenons anesthesia are commonly used anaesthetic procedures. The present study is carried out at department of ophthalmology, Government Medical College Anantapuramu, Andhra Pradesh with an objective to compare the efficacies of two commonly used techniques of anesthesia and also to assess the complications arising out of it. The study indicated that sub tenons form of anesthesia is comparatively superior over its counter part in terms of analgesia, akinesia and intraocular pressures.